Naringenin ameliorates cytotoxic effects of bisphenol A on mouse Sertoli cells by suppressing oxidative stress and modulating mitophagy: An experimental study - Layasadat Khorsandi; Abbas Heidari-Moghadam; Elham Younesi; Mohammad Javad Khodayar; Yousef Asadi-Fard (Shahid Sadoughi University of Medical Sciences, 2024)
Abstract Background: Bisphenol A (BPA), an endocrine-disrupting agent, is widely used as polycarbonate plastics for producing food containers. BPA exposure at environmentally relevant concentrations can cause reproductive disorders. Objective: The effect of Naringenin (NG) on BPA-induced Sertoli cell toxicity and its mechanism was examined in the present study. Materials and Methods: In this experimental-laboratory study, the mouse TM4 cells were treated to BPA (0.8 μM) or NG for 24 hr at concentrations of 10, 20, and 50 μg/ml. Cell viability, reactive oxygen species (ROS) production, malondialdehyde (MDA) content, antioxidant level, and mitochondrial membrane potential (MMP) were examined. The expression of mitophagy-related genes, including Parkin and PTEN-induced putative kinase 1 (Pink1), was also evaluated. Results: BPA significantly lowered the viability of the Sertoli cells (p= 0.004). Pink1 and Parkin levels of the BPA group were significantly increased (p < 0.001), while the MMP was considerably decreased (p < 0.001). BPA raised MDA and ROS levels (p < 0.001) and reduced antioxidant biomarkers (p= 0.003). NG at the 20 and 50 μg/ml concentrations could significantly improve the viability and MMP of TM4 cells (p= 0.034). NG depending on concentration, could decrease Pink1 and Parkin at mRNA and protein levels compared to the BPA group (p = 0.024). NG enhanced antioxidant factors, while ROS and MDA levels were decreased in the BPA-exposed cells. Conclusion: The beneficial impacts of NG on BPA-exposed Sertoli cells are related to the suppression of mitophagy and the reduction of oxidative stress.